KEDUDUKAN KREDITUR DALAM PEMBIAYAAN MOBIL PENUMPANG OLEH PERUSAHAAN PEMBIAYAAN DENGAN JAMINAN FIDUSIA SETELAH BERLAKUNYA PUTUSAN MAHKAMAH KONSTITUSI (MK) No 18/PUU XVII/2019 - Erika Yulianti (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
‘An agreement with a fiduciary guarantee’is an additional agreement’or assesoir of0a basic0agreement that creates an obligation for the parties to fulfill an achievement in the form of giving something, doing something0or’not doing something0that can be valued0in money.”Fiduciary must be registered and generate a fiduciary certificate (Article 11 to Article 18 Law of The Republic of Indonesia on Fiduciary). Theregistration of this0fiduciary guarantee itself gives preference. A fiduciary certificate has executorial power like a court decision. After the ‘Constitutional Court’Decision ‘No. 18 / PUU-XVII / 2019’which interpreted Article 15 section (2) and (3) of Law 42 of 1999 Law of The Republic of Indonesia on Fiduciary, had a significant impact on financing institutions as creditors where they could no longer carry out executions using The executorial title for the movable property guarantee is based on the fiduciary deed if ‘the debtor does not agree to submit the collateral object.’So the authors raised several problems, namely: how was the influence after the Constitutional Court Decision ‘No. 18 / PUU-XVII / 2019 on Article 15 section (2) and (3) Law No. execution of fiduciary guarantees; and what is the balance of the position of debtors and creditors in the agreement ‘after the Constitutional Court Decision No.18 / PUU-XVII / 2019.’After analyzes with the normative legal research method, a legal research, both pure and applied is carried out by a legal researcher to examine a norm, then after the Constitutional Court decision, if the debtor refuses to accept the breach, the default and execution must be proven through the court. As well as the balance of position still cannot be said to be balanced but the position of the debtor has increased compared to before the Constitutional Court Decision.